m6A methylation: a process reshaping the tumour immune microenvironment and regulating immune evasion - Xiaoxue Cao; Qishun Geng; Danping Fan; Qiong Wang; Xing Wang; Mengxiao Zhang; Lu Zhao; Yi Jiao; Tingting Deng; Honglin Liu; Jing Zhou; Liqun Jia; et al. (Molecular Cancer, 2023)
Abstract N6-methyladenosine (m6A) methylation is the most universal internal modification in eukaryotic mRNA. With elaborate functions executed by m6A writers, erasers, and readers, m6A modulation is involved in myriad physiological and pathological processes. Extensive studies have demonstrated m6A modulation in diverse tumours, with effects on tumorigenesis, metastasis, and resistance. Recent evidence has revealed an emerging role of m6A modulation in tumour immunoregulation, and divergent m6A methylation patterns have been revealed in the tumour microenvironment. To depict the regulatory role of m6A methylation in the tumour immune microenvironment (TIME) and its effect on immune evasion, this review focuses on the TIME, which is characterized by hypoxia, metabolic reprogramming, acidity, and immunosuppression, and outlines the m6A-regulated TIME and immune evasion under divergent stimuli. Furthermore, m6A modulation patterns in anti-tumour immune cells are summarized.